Use of Progress Testing in a UK Dental Therapy and Hygiene Educational Program. Issue 2 (1st February 2018) - Ali, Kamran; Zahra, Daniel; Tredwin, Christopher; McIlwaine, Claire; Jones, Gill
Abstract : Progress testing provides a longitudinal assessment of the development and sustainability of students' knowledge at regular intervals over the duration of an educational program. Comparisons of performance on successive tests are used to monitor growth in knowledge. The aim of this study was to evaluate the effects of progress testing in an undergraduate program for dental therapy and hygiene (DTH) students in the United Kingdom as the main tool for academic assessment. Data were collected for progress tests of all 38 DTH students from 2015 to 2017. Each test consisted of 100 single best answer multiple‐choice items with accompanying vignette. The students chose their answer from five options. A score of 1 was awarded for a correct answer, −0.25 for an incorrect answer, and 0 for don't know (DK). Three cohorts of DTH students were included in the study, and seven progress tests were conducted over a period of three years. Analysis of performance showed growth in knowledge across successive years, with the largest increase in knowledge in the transition from Year 1 to Year 2 and concomitant reduction in incorrect and DK responses. This was a pioneering study to report the establishment and use of progress testing among undergraduate DTH students. Notwithstanding the challenges involved, the study found merit in further exploring the use of progress testing for students in the DTH program.